Auditor choice and information asymmetry: Evidence from international syndicated loans - MA, Zhiming (Institutional Knowledge at Singapore Management University, 2019)
Analyzing a large sample of non-US public firms from 31 countries that obtain private loans, we find that loan syndicates that lend to borrowers that employ Big N auditors are larger and less concentrated and that the lead arrangers and largest investors of these syndicates are able to hold a lower proportion of the loan after issuance. Further analysis demonstrates that this effect exists only in countries with strong creditor rights and in those countries with high levels of societal trust, suggesting that both sound formal and informal institutional factors are prerequisites for lenders and borrowers to benefit from differential audit quality on loan syndicate structure efficiency. Furthermore, we find that the loan syndicate structure benefits for borrowers that employ Big N auditors are higher for borrowers with greater information asymmetry problems, but we do not find that Big N audits are able to address the information asymmetry and moral hazard issues between the lenders themselves.